Preparation method of intelligent coating with multistage self-repairing capability
By constructing MOF-LDH core-shell structured nanocontainers, the functional objects are released in stages, solving the problem of protection failure caused by microcracks in existing anti-corrosion coatings during service. This achieves multi-level self-repair and long-term corrosion resistance, improving the protective performance and stability of the coating.
Patent Information
- Application Number
- CN202511880237.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-02-03
AI Technical Summary
Existing anti-corrosion coatings are prone to microcracks or defects during service due to mechanical scratches, thermal stress, and other factors, leading to the penetration of corrosive media. The release of traditional corrosion inhibitors is uncontrollable, and they cannot achieve multi-level self-repair. Furthermore, they affect the mechanical properties and protective stability of the coating.
MOF-LDH core-shell nanocontainers were constructed, and functional guests were loaded in situ in stages. The pH responsiveness of MOF and the corrosive ion responsiveness of LDH were utilized to achieve the graded release of functional guests, forming a multi-level self-healing coating, which ensures the long-term corrosion resistance and mechanical stability of the coating.
It achieves multi-level self-healing of coatings under repeated damage or continuous corrosion environments, improves protective performance, significantly enhances the corrosion resistance and mechanical properties of the coating, and simplifies the preparation process and reduces costs.
Smart Images

Figure CN121450195A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of corrosion and protection technology, specifically relating to a method for preparing a smart coating with multi-level self-healing capabilities. Background Technology
[0002] Corrosion is a chemical or electrochemical deterioration process that occurs in metallic materials under natural environmental or service conditions. It not only leads to a decline in the mechanical properties of metal structures and a shortened service life, but can also cause safety accidents, resulting in huge economic losses and environmental pollution. Statistics show that global economic losses due to metal corrosion account for 3% to 5% of GDP annually, with losses in my country alone exceeding one trillion yuan annually. Metal corrosion is mainly divided into two categories: chemical corrosion and electrochemical corrosion. Electrochemical corrosion, involving processes such as electrode reactions and ion migration, causes more widespread and severe damage to metal structures.
[0003] Traditional anti-corrosion coatings employ a passive protection mechanism, forming a dense film to prevent corrosive media (such as moisture, Cl-, O2, etc.) from contacting the metal substrate, thus achieving an anti-corrosion effect. However, these coatings are prone to microcracks or defects during service due to mechanical scratches, thermal stress, environmental aging, and other factors. Once the coating fails, corrosive media can quickly penetrate to the metal substrate surface, causing localized corrosion or even accelerating coating peeling, leading to a complete loss of protective function. To address this issue, researchers have proposed adding corrosion inhibitors to the coating to achieve active protection. When defects appear in the coating, the corrosion inhibitor is released and forms a protective film on the metal surface, inhibiting the corrosion reaction. However, directly adding corrosion inhibitors has several drawbacks: first, the corrosion inhibitor easily interacts with the coating components, leading to decreased coating compatibility and deteriorated mechanical properties; second, the corrosion inhibitor easily migrates and aggregates in the coating, causing excessively high or low local concentrations, failing to achieve uniform protection; and third, the corrosion inhibitor is easily degraded by environmental media or released prematurely, resulting in a significantly shortened protective lifespan.
[0004] With high-end equipment (such as aerospace equipment, deep-sea exploration equipment, and precision machinery) placing higher demands on the long-term service capability and adaptability to complex environments of coatings, intelligent self-healing anti-corrosion coatings have become a research hotspot. These coatings can sense environmental changes (such as pH changes, corrosion ion intrusion, and mechanical damage) and trigger self-healing functions, achieving a closed-loop protection of "damage-response-repair." Currently, the self-healing mechanism of intelligent coatings mainly relies on micro / nano containers loading functional objects (corrosion inhibitors, repair agents, etc.), releasing these functional objects through container rupture, responsive degradation, and other means. For example, patent CN116925619A discloses a graphene-based two-component self-healing anti-corrosion coating, which uses graphene-based microcapsules loaded with corrosion inhibitors. When the coating is damaged, the microcapsules rupture to release the corrosion inhibitors and achieve self-repair. However, this technology can only achieve a single release and cannot meet the needs of multiple repairs. Patent CN117777820A loads corrosion inhibitors and warning agents into two different nano-containers to achieve damage self-warning and single-time self-repair, but it does not solve the problem of graded release and multi-level repair of functional objects.
[0005] Metal-organic frameworks (MOFs) are porous crystalline materials formed by coordination bonds between metal ions and organic ligands. They possess characteristics such as large specific surface area, tunable pore structure, and easy surface functionalization. Most MOFs are pH-responsive—in corrosive environments (where pH decreases), the coordination bonds of the MOF break, leading to the disintegration of the crystal structure and enabling the controlled release of the loaded functional host. Layered bimetallic hydroxides (LDHs) are layered materials composed of two metal hydroxides. They exhibit anion exchange properties and intrinsic responsiveness to corrosive ions such as Cl-. When Cl- invades in a corrosive medium, anions between the LDH layers exchange with Cl-, triggering the exfoliation of the layered structure and releasing the loaded functional host.
[0006] Although both MOF and LDH have been used as corrosion inhibitor carriers, current technologies have not combined them to construct core-shell nanocontainers, nor have they utilized their different response mechanisms to achieve graded release of functional objects and multi-level self-healing of coatings. The core shortcomings of existing technologies include: (1) a single carrier cannot achieve multiple repairs, and the carrier fails after a single release; (2) the functional object loading capacity is limited, and the release process is uncontrollable, making it impossible to match the corrosion process as needed; (3) insufficient compatibility between the carrier and the coating, which easily affects the mechanical properties and protective stability of the coating. Therefore, developing a smart coating based on a multi-response carrier, with graded release function and capable of multi-level self-healing, is of great significance for improving the long-term protective performance of metal structures.
[0007] Application content
[0008] To address the limitations of existing anti-corrosion coatings, such as passive protection, limited self-healing cycles, and uncontrollable corrosion inhibitor release, this application aims to provide a method for preparing intelligent coatings with multi-level self-healing capabilities. By constructing MOF-LDH core-shell structured nanocontainers, the different response mechanisms of the two materials are utilized to achieve graded release of functional objects. This enables the coating to achieve multi-level self-healing under repeated damage or continuous corrosion environments, while ensuring long-term corrosion resistance and mechanical stability, meeting the usage requirements of complex service environments such as high-end equipment.
[0009] The specific technical problems to be solved in this application include: providing a multi-response nanocontainer to achieve graded loading and controllable release of functional objects, avoiding the failure of repair capabilities caused by single release; coordinating the fabrication processes of the MOF core and LDH shell to ensure the integrity and stability of the core-shell structure while increasing the loading capacity of functional objects; optimizing the compatibility between the nanocontainer and the organic coating to avoid a decrease in the mechanical properties of the coating due to the addition of fillers; and matching the release rate of the functional objects with the corrosion process through process parameter control to achieve on-demand and timely multi-level self-repair.
[0010] To achieve the above objectives, the core technical solution adopted in this application is as follows: constructing a "MOF core-LDH shell" core-shell structured nanocontainer, loading two functional guests in situ in stages, utilizing the pH responsiveness of MOF and the corrosive ion responsiveness of LDH to achieve the graded release of functional guests, adding the nanocontainer to an organic coating, and constructing a smart coating with multi-level self-healing capabilities.
[0011] This application provides a method for preparing a smart coating with multi-level self-healing capabilities, including the following core steps:
[0012] (1) A core-shell structured nanocontainer with a graded release function is prepared, wherein the nanocontainer has a metal-organic framework compound (MOF) as the core and a layered bimetallic hydroxide (LDH) as the shell;
[0013] (2) Functional object 1 and functional object 2 are loaded in the core and shell respectively using the stepwise in-situ loading method;
[0014] (3) The core-shell structured nanocontainer is added as a filler to the organic coating solution, adheres to the surface of the metal substrate and is dried to obtain a smart coating with multi-level self-healing ability.
[0015] As a preferred embodiment, the raw materials for preparing the metal-organic framework compound (MOF) include metal salt 1, which is selected from one or more of zinc nitrate, cobalt nitrate, zinc acetate, and cobalt acetate hydrate, preferably one or two of zinc nitrate hexahydrate and cobalt nitrate hexahydrate.
[0016] As a preferred embodiment, the raw material for preparing the layered bimetallic hydroxide (LDH) includes metal salt 2, which is selected from one or more of the hydrates of zinc nitrate, cobalt nitrate, nickel nitrate, aluminum nitrate, and magnesium nitrate, and preferably one or more of nickel nitrate hexahydrate, cobalt nitrate hexahydrate, and aluminum nitrate nonahydrate.
[0017] As a preferred embodiment, the organic ligand is selected from one or more of 2,5-furandicarboxylic acid, terephthalic acid, 1,3,5-pyromellitic acid, and 2-methylimidazole, preferably one or two of 2,5-furandicarboxylic acid and 2-methylimidazole.
[0018] As a preferred embodiment, the solvent is selected from one or more of deionized water, methanol, ethanol, and N,N-dimethylformamide; wherein, the solvent for preparing LDH needs to have CO2 removed beforehand, and the removal method is one or more of inert gas aeration, distillation and boiling.
[0019] As a preferred embodiment, the functional guest 1 is an organic corrosion inhibitor selected from one or more of 8-hydroxyquinoline, benzotriazole, and 2-mercaptobenzothiazole; the functional guest 2 is an organic or inorganic corrosion inhibitor selected from one or more of 8-hydroxyquinoline, vanadate, tungstate, and molybdate; the functional guest 1 is preferentially released through the pH-responsiveness of the MOF, and the functional guest 2 is subsequently released through the corrosive ion-responsiveness of the LDH, thus achieving a staged release.
[0020] As a preferred embodiment, the preparation process parameters of the core-shell structured nanocontainer are as follows: (1) The growth temperature of the MOF core is 25-80℃, the growth time is 12-48h, the molar concentration of metal salt 1 is 0.1-0.5mol / L, the molar concentration of organic ligand is 0.5-5mol / L, and the molar concentration of functional guest 1 is 0.01-0.1mol / L; (2) The etching growth temperature of the LDH shell is 20-80℃, the growth time is 12-48h, the molar concentration of metal salt 2 is 0.02-0.2mol / L, the molar concentration of functional guest 2 is 0.002-0.02mol / L, and the mass concentration of MOF core powder is 1-10g / L.
[0021] As a preferred embodiment, the amount of the core-shell structured nanocontainer added to the organic coating is 0.05% to 10% of the coating mass, preferably 0.1% to 5%.
[0022] As a preferred embodiment, the organic coating is selected from one or more of epoxy resin coating, acrylic resin coating, polyurethane coating, and sol-gel coating; the method by which the solution adheres to the surface of the metal substrate is one or more of dip-coating, coating, and spraying, wherein the dip-coating speed is 1000-2000 μm / s, the coating height is 50-200 μm, and the spraying pressure is 2-6 kPa.
[0023] This application also provides a smart coating obtained by any of the methods described above.
[0024] This application also provides the application of the above-mentioned smart coating, which is suitable for corrosion protection of metal substrates such as aluminum alloy, steel, and copper alloy, and is especially suitable for metal structure protection in marine environments, industrial corrosive environments, and high-end equipment service environments.
[0025] To illustrate this more clearly, the technical solution of this application is described in detail below. The specific technical solution is as follows:
[0026] Step 1: Fabrication of core-shell structured nanocontainers:
[0027] (1) Preparation of MOF cores and loading of functional guest 1:
[0028] Metal salt 1, organic ligand, functional guest 1 and solvent were selected as raw materials, and MOF cores loaded with functional guest 1 were prepared by in-situ coating method.
[0029] As a preferred option, metal salt 1 is selected from one or more of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, zinc acetate dihydrate, and cobalt acetate tetrahydrate.
[0030] Further preferred are zinc nitrate hexahydrate and cobalt nitrate hexahydrate, with a molar concentration of 0.1–0.5 mol / L. This concentration range can ensure sufficient growth of MOF crystals while avoiding agglomeration caused by excessive metal ions.
[0031] As a preferred option, the organic ligand is selected from one or more of 2,5-furandicarboxylic acid, terephthalic acid, 1,3,5-pyromellitic acid, and 2-methylimidazole.
[0032] Further preferred are 2,5-furandicarboxylic acid and 2-methylimidazole, with a molar concentration of 0.5–5 mol / L. An excess of organic ligands can ensure sufficient coordination of metal ions to form a structurally complete MOF crystal.
[0033] As a preferred embodiment, the functional guest 1 is an organic corrosion inhibitor selected from one or more of 8-hydroxyquinoline, benzotriazole, and 2-mercaptobenzothiazole, with a molar concentration of 0.01 to 0.1 mol / L. This concentration ensures that the functional guest 1 is fully loaded in the MOF pores without affecting the MOF crystal structure.
[0034] As a solvent, one or more of deionized water, methanol, and ethanol can be selected, with methanol and ethanol being preferred. The solvent must ensure that the raw material is fully dissolved and does not react with the functional guest.
[0035] The preparation process is as follows: Metal salt 1, organic ligand, and functional guest 1 are dissolved in solvents respectively. The organic ligand solution and the functional guest 1 solution have the same volume, and the volume of the metal salt 1 solution is 0.5 to 2.5 times the sum of the volumes of the former two. After the three solutions are mixed evenly, they are stirred at 25 to 80°C for 1 to 2 hours, and then aged for 12 to 48 hours for crystal growth. After the growth is completed, the crystals are centrifuged (8000 to 12000 r / min), washed (washed with solvent 3 to 5 times), dried (vacuum dried at 60 to 80°C for 12 to 24 hours), and ground to obtain MOF core powder loaded with functional guest 1.
[0036] (2) Preparation of LDH shell and loading of functional guest 2:
[0037] Using MOF core powder loaded with functional guest 1, metal salt 2, functional guest 2 and solvent treated with CO2 removal as raw materials, LDH shell loaded with functional guest 2 was prepared by anion exchange method to form a core-shell structured nanocontainer.
[0038] As a preferred option, metal salt 2 is selected from one or more of zinc nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, aluminum nitrate nonahydrate, and magnesium nitrate hexahydrate.
[0039] Further preferred materials are nickel nitrate hexahydrate, cobalt nitrate hexahydrate, and aluminum nitrate nonahydrate, with a molar concentration of 0.02–0.2 mol / L. This concentration ensures that the LDH layer grows uniformly on the MOF core surface, forming a dense shell.
[0040] As a preferred embodiment, the functional object 2 is selected from one or more of 8-hydroxyquinoline, vanadates (sodium metavanadate, potassium vanadate), tungstates (sodium tungstate, potassium tungstate), and molybdates (sodium molybdate, potassium molybdate).
[0041] Further preferred materials are sodium metavanadate, sodium tungstate, and 8-hydroxyquinoline, with a molar concentration of 0.002–0.02 mol / L. Functional guest 2 is loaded onto the LDH interlayer via anion exchange, and this concentration ensures a balance between the loading amount and the release rate.
[0042] The solvent can be selected from one or more of methanol, ethanol, and N,N-dimethylformamide, preferably ethanol or N,N-dimethylformamide. The solvent needs to be pre-removed of CO2 (by purging with inert gas for 30-60 min or by distillation and boiling for 10-15 min) to avoid CO2 reacting with metal ions to generate carbonate impurities, which would affect the LDH shell structure.
[0043] Preparation process parameters: Metal salt 2, MOF core powder, and functional guest 2 are sequentially added to a CO2-free solvent. The mass concentration of MOF core powder is 1-10 g / L. The mixture is stirred at 20-80℃ for 12-48 h to carry out LDH etching growth and functional guest 2 loading. After growth, the mixture is centrifuged (8000-12000 r / min), washed (washed with solvent 3-5 times), dried (vacuum dried at 60-80℃ for 12-24 h), and ground to obtain core-shell structured nanocontainer powder loaded with two functional guests.
[0044] Step 2: Preparation of the smart coating:
[0045] Prepare the organic coating solution: Select one or more of epoxy resin, acrylic resin, polyurethane resin, and sol-gel as the coating matrix, dissolve the resin in the corresponding solvent (e.g., epoxy resin dissolved in acetone, acrylic resin dissolved in methyl ethyl ketone), and stir until uniform and transparent.
[0046] Adding nanocontainers: Add core-shell structured nanocontainer powder to the organic coating solution. The amount of nanocontainers added is 0.05% to 10% of the coating mass, preferably 0.1% to 5%. Stir at room temperature for 2 to 4 hours to ensure that the nanocontainers are uniformly dispersed and do not agglomerate.
[0047] Coating and Curing: The coating solution is applied to the surface of the metal substrate (which has been pre-polished, degreased, and derusted) using the dip-coating, coating, or spraying methods. The dip-coating speed is 1000–2000 μm / s, the coating height is 50–200 μm, the coating speed is 800–1200 μm / s, and the spraying pressure is 2–6 kPa. The coated metal substrate is then placed in a dark, ventilated place or a drying oven for curing. The curing conditions are adjusted according to the type of coating (e.g., epoxy resin coatings are cured at room temperature for 5–7 days, and sol-gel coatings are dried at 60℃ for 2 hours followed by drying at 120℃ for 1 hour). The final product is an intelligent coating with multi-level self-healing capabilities.
[0048] The following section provides a detailed explanation of the principles of the technical solution presented in this application and the beneficial effects it produces.
[0049] This application is the first to construct a "MOF core-LDH shell" core-shell structure, achieving the graded release of two functional guests through stepwise in-situ loading. The MOF core has a high specific surface area and abundant porosity, which can efficiently load organic corrosion inhibitors (functional guest 1). Furthermore, the pH responsiveness of the MOF causes it to preferentially disintegrate at coating defects (when corrosion occurs and the pH drops to 2-5), rapidly releasing functional guest 1 and forming a dense protective film on the metal surface, achieving the first level of self-repair. The LDH shell has anion exchange properties; when the loaded functional guest 2 (inorganic or organic corrosion inhibitor) invades in the corrosive medium (Cl- concentration > 0.01 mol / L), it is released through ion exchange, further repairing corrosion sites on the metal surface, achieving the second level of self-repair. Test examples show that this graded release mechanism causes the open circuit potential of the coating to first recover within 1-2 hours after artificial scratching (first level of repair), and then recover a second time within 10-12 hours (second level of repair), while the open circuit potential of traditional coatings continuously decreases, showing no repair phenomenon.
[0050] This application optimizes the types and concentrations of metal salts, organic ligands, and functional guests to ensure the integrity and stability of the core-shell structure. For example, using zinc nitrate and cobalt nitrate as metal salts 1 can form stable ZIF-8 and ZIF-67 type MOF cores with high porosity, increasing the loading capacity by more than 30% compared to other MOFs. The LDH shell uses nickel, cobalt, and aluminum-based metal salts, which enhances the bonding force between the shell and the MOF core, preventing shell detachment during service. Simultaneously, the combination of solvent decoupling, in-situ coating, and anion exchange effectively prevents premature release of functional guests, ensuring the stability of the coating when undamaged. Electrochemical testing shows that after immersion in 3.5 wt% NaCl aqueous solution for 60 days, the low-frequency impedance modulus (|Z| 0.01 Hz) of the coating prepared in this application remains at 10. 8 Ω·cm 2 The above is a comparison with the blank coating (approximately 2×10). 5 Ω·cm 2 It improves by 3 orders of magnitude, and its long-term corrosion resistance is significantly enhanced.
[0051] Strict control was exercised over the particle size of the core-shell structured nanocontainers, limiting them to the range of 300–500 nm. This resulted in good compatibility with organic coatings. When the addition amount was within the range of 0.05%–10%, the coating's adhesion (reaching level 1 in the cross-cut test) and hardness (reaching 2H in pencil hardness) showed no significant decrease, significantly improving upon the agglomeration problem of traditional nanofillers (such as graphene and carbon nanotubes). This effect is attributed to the interaction between the surface functional groups (such as hydroxyl and carboxyl groups) of the MOF core and LDH shell and the resin molecules, forming a stable interfacial bond. This ensures both the mechanical properties of the coating and the uniform dispersion of the nanocontainers.
[0052] Furthermore, the preparation process of this application does not require high-temperature and high-pressure equipment. The reaction temperature is controlled at 20–80°C, and the reaction time is 12–48 hours. The centrifugation and drying steps are all conventional processes, resulting in lower costs. Compared with existing nanocontainers that require complex modifications (such as surface grafting and polymer coating), the core-shell structure of this application is directly constructed through in-situ reaction, simplifying the steps, improving production efficiency, and using commercially available conventional chemicals as raw materials, making it easy to scale up production. Attached Figure Description
[0053] Figure 1 Example 1: X-ray diffraction (XRD) patterns of nanocontainers prepared in Comparative Examples 1-3.
[0054] Figure 2 Transmission electron microscopy-energy dispersive spectroscopy (TEM-EDS) image of the core-shell structured nanocontainer (ZIF-8 / MBT@LDH-Q) prepared in Example 1.
[0055] Figure 3 The stepwise release UV-Vis spectrophotometric spectrum of the core-shell structured nanocontainer (ZIF-8 / MBT@LDH-Q) prepared in Example 1 in a 3.5 wt% NaCl aqueous solution at pH 3.
[0056] Figure 4 Electrochemical test results of coatings prepared in Example 1 (ZMLQ / EP) and Comparative Example 4 (EP).
[0057] exist Figure 1 In the spectrum, the products involved include ZIF-8 powder of Comparative Example 1, ZIF-8 / MBT powder of Comparative Example 2, ZIF-8 / MBT@LDH powder of Comparative Example 3, and ZIF-8 / MBT@LDH-Q powder of core-shell structured nanocontainer of Example 1; the horizontal axis of the spectrum is the diffraction angle 2θ in °, and the vertical axis is the unitless relative diffraction intensity.
[0058] exist Figure 2 In the test image, the core-shell structured nanocontainer (ZIF-8 / MBT@LDH-Q) prepared in Example 1 is shown. The detectable elemental signals include C and N elements from the ZIF-8 organic ligand, S element from the functional guest 1MBT, Zn element from ZIF-8 metal salt 1, and Co and Ni elements from LDH metal salt 2. At the same time, the core-shell structure with a particle size of about 400 nm can be observed as a whole. The scale bar in the test image is 200 nm.
[0059] exist Figure 3In the spectrophotometric spectrum, the test environment was a 3.5 wt% NaCl aqueous solution with pH=3, which can show the characteristic absorption peak of functional guest 2 (8-HQ) at a wavelength of 325 nm and the characteristic absorption peak of functional guest 1 (MBT) at a wavelength of 345 nm. The spectrum includes release curves at multiple time points of 0h, 1h, 2h, 4h, 6h, 24h, and 48h. The horizontal axis is wavelength (unit: nm) and the vertical axis is unitless absorbance.
[0060] Figure 4 It contains four subgraphs.
[0061] Figure 4 (a) is the Nyquist plot. The test objects include ZMLQ / EP coatings soaked for 0 days, ZMLQ / EP coatings soaked for 60 days, EP coatings soaked for 0 days, and EP coatings soaked for 60 days. The horizontal axis is the real part impedance Z' (unit: Ω·cm). 2 The vertical axis represents the imaginary impedance Z (unit: Ω·cm). 2 ).
[0062] Figure 4 (b) shows the AC impedance spectrum, with the test object and... Figure 4 (a) Consistent, the horizontal axis represents frequency (unit: Hz), and the vertical axis represents impedance modulus |Z| (unit: Ω·cm). 2 ).
[0063] Figure 4 (c) is the corresponding Figure 4 (b) Phase angle spectrum, test object and Figure 4 (a) Consistent, with the horizontal axis representing frequency (in Hz) and the vertical axis representing phase angle (in °).
[0064] Figure 4 (d) shows the open circuit potential test curve. The test objects are the ZMLQ / EP coating and the EP coating after scratching. The first self-healing potential rise point at 1.5h and the second self-healing potential rise point at 11h can be observed. The horizontal axis is time (unit: h) and the vertical axis is the open circuit potential relative to the Ag / AgCl reference electrode (unit: V). Detailed Implementation
[0065] The technical solution of this application will be described in detail below through specific embodiments. The raw materials used in the embodiments are all commercially available products and have not undergone further purification treatment. The metal matrix is made of aluminum alloy (type 6061), which is polished step by step with 120-800 grit sandpaper, degreased with acetone, rinsed with deionized water, and dried at 60°C before use.
[0066] Example 1
[0067] (1) Preparation of MOF cores (ZIF-8 / MBT)
[0068] 9 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 90 mmol of 2-methylimidazole (C4H6N2), and 1 mmol of 2-mercaptobenzothiazole (MBT, functional guest 1) were weighed and dissolved in 60 mL, 30 mL, and 30 mL of methanol, respectively, and stirred until completely dissolved. The three solutions were slowly mixed and magnetically stirred at 25 °C for 1 h to ensure uniform dispersion. The mixture was then transferred to a sealed reactor and aged at 25 °C for 24 h to promote MOF crystal growth and in-situ loading of functional guest 1. After the reaction was completed, the mixture was centrifuged at 10000 r / min for 10 min and the precipitate was collected. The precipitate was washed three times with methanol to remove unreacted raw materials and impurities, and then dried in a vacuum drying oven at 60 °C for 12 h. After grinding, the MBT-loaded ZIF-8 powder (ZIF-8 / MBT) with a particle size of approximately 300 nm was obtained.
[0069] (2) Fabrication of core-shell structured nanocontainers (ZIF-8 / MBT@LDH-Q)
[0070] 50 mL of ethanol was used as a solvent, and nitrogen gas was purged for 30 min to remove CO2, preventing the formation of carbonate impurities that could affect the LDH shell structure. To the CO2-free ethanol, 0.55 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.55 mmol of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.16 g of the aforementioned ZIF-8 / MBT powder, and 1 mmol of 8-hydroxyquinoline (8-HQ, functional guest 2) were added sequentially. The mixture was magnetically stirred at 25 °C for 24 h, achieving the etching growth of the LDH shell on the MOF core surface and the loading of functional guest 2 through anion exchange. After the reaction was complete, the mixture was centrifuged at 10000 r / min for 10 min, and the precipitate was collected. The precipitate was washed three times with ethanol, dried under vacuum at 60 °C for 12 h, and then ground to obtain core-shell structured nanocontainer powder (ZIF-8 / MBT@LDH-Q) with a particle size of approximately 400 nm.
[0071] (3) Preparation of smart coating (ZMLQ / EP)
[0072] Weigh 18g of epoxy resin (E-51) and dissolve it in 15g of acetone. Stir for 30 minutes until a uniform and transparent resin solution is formed. Add 0.015g of ZIF-8 / MBT@LDH-Q powder (the amount of nanocontainers added is 0.05% of the coating mass) to the solution and magnetically stir at room temperature for 2 hours to ensure that the nanocontainers are uniformly dispersed and free from agglomeration. Then add 6g of polyamide curing agent (type 650) and stir for 15 minutes until uniformly mixed. Apply the coating solution to the pretreated aluminum alloy surface using the dip-coating method at a dipping speed of 1667μm / s. After coating, cure in a dark and ventilated place at room temperature for 5 days to obtain a smart coating sample with multi-level self-healing capabilities.
[0073] Example 2
[0074] (1) Preparation of MOF cores (ZIF-67 / BTA)
[0075] 40 mmol of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 240 mmol of 2-methylimidazole (C4H6N2), and 3 mmol of benzotriazole (BTA, functional guest 1) were weighed and dissolved in 120 mL, 60 mL, and 60 mL of ethanol, respectively. The solutions were ultrasonically dispersed for 10 min to accelerate dissolution. The three solutions were mixed and magnetically stirred at 45 °C for 1 h, then transferred to a constant temperature reaction chamber and aged at 45 °C for 48 h to complete ZIF-67 crystal growth and BTA loading. After the reaction, the precipitate was collected by centrifugation at 12000 r / min for 10 min; washed three times with ethanol; dried under vacuum at 70 °C for 16 h; and ground to obtain BTA-loaded ZIF-67 powder (ZIF-67 / BTA) with a particle size of approximately 350 nm.
[0076] (2) Fabrication of core-shell structured nanocontainers (ZIF-67 / BTA@LDH-V)
[0077] 60 mL of deionized water was measured, distilled, and boiled for 15 min to remove CO2. After cooling to room temperature, the water was transferred to a three-necked flask. 1.5 mmol of nickel nitrate hexahydrate (Ni(NO3)2·6H2O), 0.6 g of ZIF-67 / BTA powder, and 1 mmol of sodium metavanadate (NaVO3, functional guest 2) were added sequentially. The mixture was magnetically stirred at 50 °C for 36 h, forming an LDH shell on the MOF core surface through an etching-growth mechanism, achieving anion exchange loading of vanadate. After the reaction was complete, the mixture was centrifuged at 12000 r / min for 10 min, and the precipitate was collected. The precipitate was washed three times with deionized water, vacuum dried at 70 °C for 16 h, and then ground to obtain core-shell structured nanocontainer powder (ZIF-67 / BTA@LDH-V) with a particle size of approximately 450 nm.
[0078] (3) Preparation of smart coating (ZBLV / SG)
[0079] Preparation of the sol-gel coating solution: Mix 7 mL of deionized water with 15 mL of anhydrous ethanol, slowly add 12 mL of 3-glycidyl etheroxypropyltrimethoxysilane (KH-560), and stir for 30 min to obtain solution 1; mix 6 mL of anhydrous ethanol, 3 mL of ethyl acetoacetate, and 6 mL of tetraethyl silicate, add 0.6 mL of glacial acetic acid to adjust the pH to 4-5, and stir at room temperature for 1 h to obtain solution 2. Add solution 2 dropwise to solution 1, stir for 30 min, then add 100 mg of ZIF-67 / BTA@LDH-V powder (the amount of nano-container added is 0.33% of the coating mass), and age at room temperature for 24 h. Apply the coating solution to the aluminum alloy surface using a spraying method (spraying pressure 4 kPa). After coating, dry at 60℃ for 2 h, then heat to 120℃ for 1 h, and cool with the furnace to obtain the smart coating sample.
[0080] Example 3
[0081] (1) Preparation of MOF cores (Zn-MOF / BTA)
[0082] 20 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 60 mmol of 2,5-furandicarboxylic acid (C6H4O5), and 6 mmol of benzotriazole (BTA, functional guest 1) were weighed and dissolved in 40 mL, 30 mL, and 60 mL of N,N-dimethylformamide (DMF), respectively, and stirred until completely dissolved. The three solutions were mixed and transferred to a hydrothermal reactor, and the reaction was carried out at 80 °C for 48 h to achieve dense growth of Zn-MOF crystals and efficient loading of BTA. After the reaction, the mixture was allowed to cool naturally to room temperature, centrifuged at 10000 r / min for 15 min, and the precipitate was collected. The precipitate was washed three times with DMF to remove residual ligands and unloaded corrosion inhibitors, dried under vacuum at 80 °C for 24 h, and then ground to obtain BTA-loaded Zn-MOF powder (Zn-MOF / BTA) with a particle size of approximately 320 nm.
[0083] (2) Fabrication of core-shell structured nanocontainers (Zn-MOF / BTA@LDH-W)
[0084] 50 mL of ethanol was measured, distilled, and boiled for 10 min to remove CO2. After cooling, nitrogen gas was introduced for protection. 5 mmol of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.36 g of Zn-MOF / BTA powder, and 1.5 mmol of sodium tungstate (Na2WO4·2H2O, functional guest 2) were added sequentially. The mixture was magnetically stirred at 60 °C for 20 h to achieve uniform coating of the LDH shell and loading of tungstate. After the reaction was complete, the mixture was centrifuged at 10000 r / min for 15 min, and the precipitate was collected. The precipitate was washed three times with ethanol, dried under vacuum at 80 °C for 24 h, and then ground to obtain core-shell structured nanocontainer powder (Zn-MOF / BTA@LDH-W) with a particle size of approximately 420 nm.
[0085] (3) Preparation of smart coating (ZnBLW / AR)
[0086] Weigh 21g of acrylic resin powder and dissolve it in 48g of butanone. Stir for 2 hours to form a uniform and transparent resin solution. Add 0.015g of Zn-MOF / BTA@LDH-W powder (the amount of nanocontainers added is 0.05% of the coating mass) to the solution and stir magnetically at room temperature for 3 hours to ensure that the nanocontainers are not agglomerated and are uniformly dispersed. Apply the coating solution to the aluminum alloy surface using a coating method (coating height 100μm, coating speed 1000μm / s). After coating, cure in a dark and ventilated place at room temperature for 7 days to obtain the smart coating sample.
[0087] Comparative Example 1 (blank coating, no nanocontainer)
[0088] Weigh 18g of epoxy resin (E-51) and dissolve it in 15g of acetone. Stir for 30 minutes until homogeneous and transparent. Add 6g of polyamide curing agent (type 650) and continue stirring for 15 minutes until uniformly mixed. Apply the coating solution to the pretreated aluminum alloy surface using the dip-coating method (coating speed 1667μm / s). Cure at room temperature in the dark and in a ventilated environment for 5 days to obtain a blank coating sample (EP), which is used to compare the effect of the nanocontainer on improving the protective performance of the coating.
[0089] Comparative Example 2 (single MOF support, without LDH shell)
[0090] The MBT-loaded ZIF-8 powder (ZIF-8 / MBT) was prepared according to step 1 of Example 1, and the preparation process was completely consistent.
[0091] Weigh 18g of epoxy resin (E-51), dissolve it in 15g of acetone, and stir for 30min; add 0.015g of ZIF-8 / MBT powder (the amount added is the same as in Example 1, which is 0.05% of the coating mass), and stir at room temperature for 2h;
[0092] Add 6g of polyamide curing agent, stir evenly, and then coat the aluminum alloy surface using the dip-coating method (coating speed 1667μm / s). Cure at room temperature in the dark and in a ventilated place for 5 days to obtain a single MOF carrier coating sample (ZIF-8 / MBT / EP), which is used to compare the performance differences between the core-shell structure and the single carrier.
[0093] Comparative Example 3 (single LDH vector, without MOF core)
[0094] (1) Preparation of a single LDH carrier (LDH-V)
[0095] 60 mL of deionized water was measured, distilled and boiled for 15 min to remove CO2, cooled and then 1.5 mmol of nickel nitrate hexahydrate and 1 mmol of sodium metavanadate were added. The mixture was stirred at 50 °C for 36 h. After centrifugation (12000 r / min, 10 min), washing with deionized water three times, and vacuum drying at 70 °C for 16 h, a single LDH powder loaded with vanadate (LDH-V) was obtained.
[0096] (2) Coating preparation (LDH-V / EP)
[0097] Weigh 18g of epoxy resin, dissolve it in 15g of acetone, add 0.015g of LDH-V powder (the amount added is the same as in Example 1), stir at room temperature for 2h; add 6g of polyamide curing agent, stir evenly, and then dip-coat (1667μm / s), cure at room temperature for 5 days to obtain a single LDH carrier coating sample, which is used to compare the graded release effect of core-shell structure and single LDH carrier.
[0098] Comparative Example 4 (Core-shell vector, non-functional guest)
[0099] (1) Preparation of core-shell vectors with non-functional guests (ZIF-8@LDH)
[0100] ZIF-8 core without functional guest 1 was prepared according to step 1 of Example 1 (only zinc nitrate hexahydrate and 2-methylimidazole were added, without MBT); LDH shell without functional guest 2 was prepared according to step 2 of Example 1 (only metal salt 2 and ZIF-8 core were added, without 8-HQ). After centrifugation, washing and drying, the core-shell carrier powder without functional guest (ZIF-8@LDH) was obtained.
[0101] (2) Coating preparation (ZIF-8@LDH / EP)
[0102] Weigh 18g of epoxy resin, dissolve it in 15g of acetone, add 0.015g of ZIF-8@LDH powder (the amount added is the same as in Example 1), stir at room temperature for 2h; add 6g of polyamide curing agent, stir evenly, and then dip-coat (1667μm / s), cure at room temperature for 5 days to obtain a core-shell carrier coating sample without functional object, which is used to verify the key role of functional object loading in self-healing performance.
[0103] Test Example 1: X-ray Diffraction (XRD) Test
[0104] X-ray diffractometer (Rigaku D / Max-2500) was used to perform XRD tests on the core-shell nanocontainers of Examples 1-3, ZIF-8 / MBT of Comparative Example 2, LDH-V of Comparative Example 3, and ZIF-8@LDH powder samples of Comparative Example 4. Test conditions: Cu target Kα rays (λ = 0.15406 nm), tube voltage 40 kV, tube current 100 mA, scanning range 2θ = 5°–60°, scanning speed 5° / min.
[0105] Test results: In the XRD patterns of the core-shell supports in Examples 1 to 3, the characteristic diffraction peaks of the corresponding MOF core (ZIF-8 / ZIF-67 / Zn-MOF) and LDH shell appeared simultaneously, and there were no impurity peaks, proving that the core-shell structure was successfully synthesized; Comparative Example 2 only showed the characteristic peak of ZIF-8, Comparative Example 3 only showed the characteristic peak of LDH, and the diffraction peaks of Comparative Example 4 were consistent with those of Example 1 (no functional guest did not change the crystal structure), indicating that the functional guest loading did not destroy the crystal integrity of the support.
[0106] Test Example 2: Transmission Electron Microscopy-Energy Dispersive Spectroscopy (TEM-EDS) Test
[0107] The morphology and elemental distribution of the core-shell nanocontainers in Examples 1-3 were analyzed using a transmission electron microscope (model: JEOL JEM-2100) combined with an energy dispersive spectroscopy (EDS) instrument.
[0108] Test results: The nanocontainers in Examples 1-3 all exhibited clear core-shell structures with particle sizes concentrated between 380 and 450 nm, and the boundaries between the core and shell were clear. EDS elemental distribution showed that the characteristic elements corresponding to functional guest 1 (S from MBT, N from BTA) were mainly concentrated in the core, while the characteristic elements corresponding to functional guest 2 (O from 8-HQ, V from vanadate, W from tungstate) were mainly concentrated in the shell, proving that the two functional guests were successfully loaded into the core and shell respectively, realizing a hierarchical loading design.
[0109] Test Example 3: Staged Release Performance Test
[0110] The core-shell structured nanocontainer powders from Examples 1-3 were dispersed in a 3.5 wt% NaCl aqueous solution (concentration 1 g / L) at pH 3. Release experiments were conducted at room temperature, and samples were taken at different time points. The absorbance of the released liquid was measured using a UV-Vis spectrophotometer (model: Shimadzu UV-2550) to analyze the release pattern of the functional object.
[0111] Test results: In Example 1, functional guest 2 (8-HQ) showed a characteristic absorption peak after 1 hour and reached release equilibrium after 24 hours; functional guest 1 (MBT) showed a characteristic absorption peak (wavelength 345nm) after 24 hours and the absorbance stabilized at 0.76 after 48 hours, reaching release equilibrium, clearly showing a hierarchical pattern of "shell guest released first, core guest released later".
[0112] In Example 2, the characteristic absorption peak (wavelength 400 nm) of functional guest 2 (vanadate) appeared after 2 hours and reached release equilibrium (absorbance 0.79) after 36 hours; the characteristic absorption peak (wavelength 259 nm) of functional guest 1 (BTA) initiated release after 36 hours and reached release equilibrium (absorbance 0.68) after 72 hours, consistent with the graded release mechanism in Example 1, verifying the versatility of different MOF-LDH combinations with functional guests.
[0113] In Example 3, the characteristic absorption peak (wavelength 350 nm) of functional guest 2 (tungstate) appeared after 1.5 h and reached release equilibrium (absorbance 0.85) after 30 h; the characteristic absorption peak (wavelength 259 nm) of functional guest 1 (BTA) started release after 30 h and reached release equilibrium (absorbance 0.71) after 60 h, further demonstrating the core-shell structure's ability to hierarchically load and controllably release different functional guests.
[0114] Comparative test results: Comparative Example 2 (single MOF support) showed an MBT release peak only after 24 hours, with no subsequent release process; Comparative Example 3 (single LDH support) showed a vanadate release peak only after 36 hours, with no stepwise effect; Comparative Example 4 (no functional guest) did not detect any characteristic absorption peaks, proving that the loading of the functional guest is the core of the release performance, and the core-shell structure is the key to achieving stepwise release.
[0115] Test Example 4: Electrochemical Performance Test
[0116] Electrochemical performance tests were conducted on the coating samples of Examples 1-3 and Comparative Examples 1-4 using an electrochemical workstation (model: Wuhan Corrtest CS350) to verify the corrosion resistance and self-healing ability of the coatings. The test system was a three-electrode system: the working electrode was the coating sample (test area 1 cm²). 2The reference electrode was a saturated Ag / AgCl electrode, the counter electrode was a platinum mesh, and the electrolyte was a 3.5 wt% NaCl aqueous solution (simulating a marine corrosion environment). The test temperature was room temperature (25℃). Test items included electrochemical impedance spectroscopy (EIS, frequency range 10 Hz). -2 ~10 5 Hz, disturbance potential 10mV) and open circuit potential (OCP, test duration 72h).
[0117] Test results:
[0118] (1) Electrochemical impedance spectroscopy (EIS) analysis:
[0119] When immersed for 0 days, the low-frequency impedance modulus (|Z|) of the coatings in Examples 1-3 0.01 The Hz values are 1.5 × 10⁻⁶. 9 Ω·cm 2 2.3×10 9 Ω·cm 2 1.8×10 9 Ω·cm 2 All were significantly higher than those of Comparative Example 1 (blank coating, 2.3 × 10⁻⁶). 8 Ω·cm 2 Comparative Example 2 (3.6 × 10) 8 Ω·cm 2 Comparative Example 3 (4.1×10) 8 Ω·cm 2 Comparative Example 4 (5.2 × 10⁻⁶) 8 Ω·cm 2 This demonstrates that the addition of core-shell structured nanocontainers can significantly improve the initial density and barrier properties of the coating.
[0120] After immersion for 60 days, the low-frequency impedance modulus of the coatings in Examples 1-3 remained at 1.2 × 10⁻⁶. 8 Ω·cm 2 8.5×10 8 Ω·cm 2 5.3×10 8 Ω·cm 2 The corrosion resistance degrades slowly; while the low-frequency impedance modulus of Comparative Example 1 drops to 2.1 × 10⁻⁶. 5 Ω·cm 2 (Coating completely failed), Comparative Example 2 decreased to 3.6 × 10⁻⁶. 6 Ω·cm 2 (Failed only after a single repair), Comparative Example 3 decreased to 4.5 × 10⁻⁶. 6 Ω·cm 2 (No secondary repair capability), compared to Example 4, the value decreased to 6.3 × 10⁻⁶. 6 Ω·cm2 (Without self-healing function), which fully demonstrates that the core-shell structure and graded release mechanism of this application can significantly extend the long-term corrosion resistance life of the coating.
[0121] (2) Open circuit potential (OCP) analysis:
[0122] All coated samples underwent artificial scratch treatment (scratch length 1 cm, depth 50 μm, exposing the metal substrate), and OCP changes were continuously monitored.
[0123] The OCP of the coatings in Examples 1 to 3 all exhibited a "two-stage recovery" characteristic: In Example 1, the OCP recovered from -0.75V to -0.60V at 1.5h (first self-healing, 8-HQ release in the shell), and further recovered to -0.55V at 11h (second self-healing, MBT release in the core); In Example 2, the OCP recovered from -0.78V to -0.62V at 2.5h (vanadate release), and recovered to -0.58V at 15h (BTA release); In Example 3, the OCP recovered from -0.76V to -0.61V at 2h (tungstate release), and recovered to -0.56V at 13h (BTA release).
[0124] The OCP of Comparative Example 1 (blank coating) continued to decrease from -0.72V to -1.10V at 72h without any rebound; Comparative Example 2 (single MOF support) only showed one OCP rebound at 3h (from -0.74V to -0.63V), and then continued to decrease; Comparative Example 3 (single LDH support) only showed one OCP rebound at 5h (from -0.77V to -0.65V), without secondary repair; Comparative Example 4 (non-functional object) showed a continuous decrease in OCP to -1.08V without any rebound, clearly verifying the uniqueness and effectiveness of the "multi-level self-healing" function of this application.
[0125] Test Example 5 Mechanical Property Test
[0126] To further verify the feasibility of the coatings in practical applications, mechanical property tests were conducted on the coatings of Examples 1-3 and Comparative Examples 1-4 according to national standards:
[0127] Adhesion test: Referring to GB / T 9286-1998 "Cross-cut test for paints and varnishes", a cross-cut tester (1mm grid spacing) was used to cut a grid on the coating surface. After peeling off with 3M tape, the coating peeling was observed. The results showed that the coating adhesion of Examples 1 to 3 all reached Grade 1 (no coating peeling, only slight peeling at the grid lines), which is consistent with Comparative Example 1 (blank coating, Grade 1), proving that the core-shell structured nanocontainer has good compatibility with the coating substrate and that the interfacial bonding force did not decrease due to the addition of fillers.
[0128] Hardness test: The hardness of paints and varnishes was determined by pencil hardness tester (750g load) according to GB / T 6739-2006 "Determination of Hardness of Paint Films by Pencil Method". The results showed that the pencil hardness of the coatings in Examples 1-3 was 2H, the same as Comparative Example 1 (2H), and higher than Comparative Examples 2 (H), 3 (H), and 4 (H). This demonstrates that the introduction of the core-shell structure not only did not impair the mechanical properties of the coating, but also slightly improved the coating hardness through the reinforcing effect of nanoparticles, meeting the mechanical performance requirements for actual service.
[0129] Comparison table of parameters and performance test results between the examples and comparative examples
[0130]
[0131] Note: "Corrosion resistance time" refers to the time when obvious corrosion spots appear on the coating surface (area ≥ 0.5 mm). 2 The time for self-repair is specified; the number of times the potential rises by ≥0.1V and remains stable for more than 12 hours during the open circuit potential test is determined; all test methods are based on the corresponding national standards, and the test data is the average value of 3 parallel samples.
[0132] The core-shell structured nanocontainer prepared in this application realizes hierarchical loading and controllable release of two functional objects, enabling the coating to have two or more self-healing capabilities, thus solving the defect that traditional self-healing coatings can only repair once.
[0133] The coating exhibits significantly improved long-term corrosion resistance, maintaining good protective performance even after immersion in a 3.5wt% NaCl aqueous solution for 60 days, extending its corrosion resistance life by more than 4 times compared to the blank coating.
[0134] The nanocontainer exhibits good compatibility with the organic coating, and the coating's adhesion, hardness, and other mechanical properties remain unaffected, making it suitable for practical service environments.
[0135] Furthermore, this coating is suitable for a variety of metal substrates and complex service environments (marine, industrial corrosion, high-end equipment), with a wide range of applications.
[0136] Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. These embodiments and / or implementation methods are only used to illustrate preferred embodiments and / or implementation methods for implementing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any way. Any person skilled in the art can make some modifications or alterations to other equivalent embodiments without departing from the scope of the technical means disclosed in the present invention, but these should still be regarded as the technology or embodiments that are substantially the same as the present invention.
Claims
1. A method for preparing a smart coating with multi-level self-healing capabilities, characterized in that, The core steps include the following: (1) A core-shell structured nanocontainer with a graded release function is prepared, wherein the nanocontainer has a metal-organic framework compound (MOF) as the core and a layered bimetallic hydroxide (LDH) as the shell; (2) Functional object 1 and functional object 2 are loaded in the core and shell respectively using the stepwise in-situ loading method; (3) The core-shell structured nanocontainer is added as a filler to the organic coating solution, adheres to the surface of the metal substrate and is dried to obtain a smart coating with multi-level self-healing ability.
2. The preparation method according to claim 1, characterized in that, The raw materials for preparing the metal-organic framework (MOF) include metal salt 1, which is selected from one or more of zinc nitrate, cobalt nitrate, zinc acetate, and cobalt acetate hydrate, preferably one or two of zinc nitrate hexahydrate and cobalt nitrate hexahydrate.
3. The preparation method according to claim 1, characterized in that, The raw materials for preparing the layered bimetallic hydroxide (LDH) include metal salt 2, which is selected from one or more of the hydrates of zinc nitrate, cobalt nitrate, nickel nitrate, aluminum nitrate, and magnesium nitrate, preferably one or more of nickel nitrate hexahydrate, cobalt nitrate hexahydrate, and aluminum nitrate nonahydrate.
4. The preparation method according to claim 1, characterized in that, The organic ligand is selected from one or more of 2,5-furandicarboxylic acid, terephthalic acid, 1,3,5-pyromellitic acid, and 2-methylimidazole, preferably one or two of 2,5-furandicarboxylic acid and 2-methylimidazole.
5. The preparation method according to claim 1, characterized in that, The solvent is selected from one or more of deionized water, methanol, ethanol, and N,N-dimethylformamide; wherein, the solvent for preparing LDH needs to have CO2 removed beforehand, and the removal method is one or more of inert gas purging, distillation and boiling.
6. The preparation method according to claim 1, characterized in that, The functional guest 1 is an organic corrosion inhibitor selected from one or more of 8-hydroxyquinoline, benzotriazole, and 2-mercaptobenzothiazole; the functional guest 2 is an organic or inorganic corrosion inhibitor selected from one or more of 8-hydroxyquinoline, vanadate, tungstate, and molybdate; the functional guest 1 is preferentially released through the pH-responsiveness of MOF, and the functional guest 2 is subsequently released through the corrosive ion responsiveness of LDH, thus achieving a staged release.
7. The preparation method according to claim 1, characterized in that, The preparation process parameters of the core-shell structured nanocontainer are as follows: (1) The growth temperature of the MOF core is 25-80℃, the growth time is 12-48h, the molar concentration of metal salt 1 is 0.1-0.5mol / L, the molar concentration of organic ligand is 0.5-5mol / L, and the molar concentration of functional guest 1 is 0.01-0.1mol / L; (2) The etching growth temperature of the LDH shell is 20-80℃, the growth time is 12-48h, the molar concentration of metal salt 2 is 0.02-0.2mol / L, the molar concentration of functional guest 2 is 0.002-0.02mol / L, and the mass concentration of MOF core powder is 1-10g / L.
8. The preparation method according to claim 1, characterized in that, The amount of the core-shell structured nanocontainer added to the organic coating is 0.05% to 10% of the coating mass, preferably 0.1% to 5%.
9. The preparation method according to claim 1, characterized in that, The organic coating is selected from one or more of epoxy resin coating, acrylic resin coating, polyurethane coating, and sol-gel coating; the method by which the solution adheres to the surface of the metal substrate is one or more of dip-coating, coating, and spraying, wherein the dip-coating speed is 1000-2000 μm / s, the coating height is 50-200 μm, and the spraying pressure is 2-6 kPa.
10. The smart coating obtained by the preparation method according to any one of claims 1 to 9, characterized in that, The intelligent coating is suitable for corrosion protection of metal substrates such as aluminum alloy, steel, and copper alloy, and is especially suitable for the protection of metal structures in marine environments, industrial corrosive environments, and high-end equipment service environments.
Citation Information
Patent Citations
Graphene-based bi-component self-repairing anticorrosive coating and preparation method thereof
CN116925619A
Reversible self-early-warning and self-repairing coating and preparation method thereof
CN117777820A
Cited By
Grouting material for deep cracked rock mass and preparation method thereof
CN122167117A
Grouting material for deeply cracked rock mass and preparation method thereof
CN122167117B